Experimental and Numerical Studies of the Cavity Flows at Low Reynolds Numbers. (March 2017) - Tanase, Nicoleta – Octavia; Simionescu, Stefan-Mugur; Broboana, Diana; Balan, Corneliu
Abstract: The paper is dedicated to the experimental and numerical studies of viscous flows in cavities. The present work investigates the formation of vortical structures in two configurations: (i) the flow inside a square cavity whose lid has constant velocity(a benchmark problem in fluid dynamics), and (ii) the free surface flow over a cavity weir. The experiments are performed in an open channel, the flow rate and the fluid height upstream the body being controlled by the weir. Qualitative direct visualizations of the flow patterns are obtained in the cavity. The computations are performed in 3D flow configurations with the laminar steady and unsteady solvers implemented in Ansys Fluent. The VOF (Volume of Fluid) method is used for the free surface geometry calculation and the interface between two fluids. The numerical solutions give precise descriptions of the experimental free surface line and the vortical structures and offer an evaluation of the mixing process inside cavity.